Model Adopsi Daptasi Kurikulum 2013 dan Cambridge University bagi Madrasah - Isno (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Cambridge International Examination is a unit at Cambridge University that provides an international curriculum to be adopted in all countries. In accordance with Minister of National Education Regulation (Permendiknas) No. 22/2006, and No.23 / 2006, that schools are given the freedom to develop their education curriculum. The objectives of this study are: 1) Describe the implementation of the 2013 curriculum model and Cambridge University. 2) Describe how to adopt and adapt the 2013 curriculum and Cambridge University. 3) Describe supporting and inhibiting factors Implementation of the 2013 curriculum adaptive adoption model and Cambridge University. This study uses a qualitative approach with a phenomenological study design. Regarding the presence of researchers in qualitative research, researchers acted as the main instrument. To prove that the data in this study can be accounted for, then the technique used is triangulation, which is checking the validity of data by comparing data obtained from one source with the same data from other sources in different times and places. The results of this study concluded: 1) the 2013 curriculum adaptive adoption model and Cambridge University did not leave the Core curriculum and the main points of learning material used from the Ministry of Education and Culture (Kemendikbud) and the Ministry of Religion (Kemenag). 2) Adaptation carried out is the adjustment of certain elements that already exist in the National Education Standards by referring to the Education standards at Cambridge University, or SI / SKL following Islamic education institutions that use SI / SKL from OECD member countries. Adoption of the curriculum is to improve certain elements with other curricula that have certain special qualities or Adoption used is done after going through a mapping process between SI / SKL and SI / SKL by improving KKM and teacher quality. 3) Factors supporting adaptive adoption of 2013 curricula and Cambridge University: 1) extra principal's physical and mental performance, 2) vertical and horizontal coordination of school principals, and 3) innovative thinking of school principals 4) school committees in this case fully support school policy 5) the attitude of the people who have received socialization or at least know that they are very trusting and supportive. 6) the enthusiasm and dedication of teachers who are constantly upgrading themselves and further studies. 7) Learning facilities that meet the requirements 8) availability of funds. The inhibiting factors are: 1) Too idealistic principals so that the ranks are less able to catch up, 2) the headmaster is too careful to make adaptive adoption of the 2013 curriculum and Cambridge University not yet fully implemented, 3) school committees still lack understanding of the 2013 curriculum adaptive system Cambridge University, 4) people who did not know about this implementation, they ridiculed and sanctioned specifically with HR readiness. 5) the distribution of increasing teacher understanding is not balanced